Female Urethral Diverticulum Carcinoma: A Case Report and Literature Review - Ryo Kasahara; Tadashi Tabei; Yukio Tsuura; Kazuki Kobayashi (Case Reports in Urology)
A 48-year-old woman with a history of voiding difficulty visited our hospital. Magnetic resonance imaging revealed a periurethral tumor, which was pathologically diagnosed as an adenocarcinoma via transperineal needle biopsy. Radical cystectomy and urethrectomy were performed, and the urinary tract was reconstructed using an ileal conduit. Pathological examination of a resected specimen confirmed adenocarcinoma of the urethral diverticulum. The patient received adjuvant gemcitabine and cisplatin chemotherapy. She is alive at 5 months since the operation.